2020
DOI: 10.1002/pssr.202000054
|View full text |Cite
|
Sign up to set email alerts
|

Atomic‐Scale Interface Structure in Domain Matching Epitaxial BaBiO3 Thin Films Grown on SrTiO3 Substrates

Abstract: The electronic structures of BaBiO3 (BBO) thin films grown on SrTiO3 substrates are found to be thickness dependent. The origin of this behavior remains under debate and has been suggested to be attributed to the structural and compositional modifications at the BBO/SrTiO3 interface during the first stage of film growth. Though a wetting layer with thickness of ≈1 nm has been experimentally identified at the interface, details on the microstructures of such a layer and their effect on the subsequent film growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 48 publications
(69 reference statements)
5
22
0
Order By: Relevance
“…Figure 1a shows a representative out-of-plane X-ray diffraction (XRD) pattern of the CuFeO 2 thin films. The 2θ-ω scans were aligned and calibrated using the (002) SrTiO 3 reflection at 46.470 (a ¼ 3.905 Å). The film exhibits a series of peaks assigned to the (00.3), (00.6), (00.9), and (00.12) planes of the hexagonal delafossite structure of CuFeO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1a shows a representative out-of-plane X-ray diffraction (XRD) pattern of the CuFeO 2 thin films. The 2θ-ω scans were aligned and calibrated using the (002) SrTiO 3 reflection at 46.470 (a ¼ 3.905 Å). The film exhibits a series of peaks assigned to the (00.3), (00.6), (00.9), and (00.12) planes of the hexagonal delafossite structure of CuFeO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…[44] In some cases, a structurally modified transition layer has been reported to be formed at the interface to facilitate the heteroepitaxial growth. [45,46] Recently, domain matching epitaxy was observed for orthorhombic (111) Hf 0.5 Zr 0.5 O 2 (HZO) thin films grown on cubic (001) La 2/3 Sr 1/3 MnO 3 (LSMO) epitaxial layer through the introduction of arrays of interface dislocations with short periodic spacing. [47] In this unique case, the crystal planes of the film and substrate show an apparent symmetry dissimilarity, whereas the lattice mismatches along two in-plane matching orientations of HZO [211]//LSMO [110] and HZO [022]//LSMO [110] are calculated to be about 10% and 58%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on BBO thin films are scarce [22][23][24][25][26][27][28][29][30][31]. Most papers report on the growth and properties of BBO on SrTiO 3 (STO) substrates [22,23,25,[28][29][30][31], with both materials presenting a rather large lattice mismatch of ≈12%.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on BBO thin films are scarce [22][23][24][25][26][27][28][29][30][31]. Most papers report on the growth and properties of BBO on SrTiO 3 (STO) substrates [22,23,25,[28][29][30][31], with both materials presenting a rather large lattice mismatch of ≈12%. It was shown that this misfit is accommodated through the formation of an ultrathin interfacial δ-Bi 2 O 3 layer with a fluorite structure, which forms a coherent interface with the substrate and a semi-coherent interface with BBO [28,31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation